Correction: Serrano, J.J.; Esparcia, J. Diagnosis of Rural Development Processes Based on the Stock of Social Capital and Social Networks: Approach from E-I Index. Land 2023, 12, 850 - J. Javier Serrano; Javier Esparcia (Land, 2023)
In the original publication [...]